2017
DOI: 10.1371/journal.pone.0176965
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Smad2 signalling with loganin attenuates SW10 cell cycle arrest induced by TNF-α

Abstract: The activity of Schwann cells (SWCs) is very important in trauma-induced nerve repair, and tumour necrosis factor-α (TNF-α) produced during tissue injury inhibits the viability of SWCs, which delays the repair of peripheral nerves. Loganin is an iridoid glycoside that has been shown to alleviate a variety of cytotoxic effects. In the current study, we evaluated the potential efficacy and the mechanism of action of loganin in TNF-α-induced cytotoxicity in SW10 cells. The experimental results indicated that loga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Wang et al verified that loganin alleviates intestinal epithelial inflammation by regulating the TLR4/NF-κB and JAK/STAT3 signaling pathways [ 41 ]. Chao et al exhibited that loganin has beneficial effects on Schwann cells by blocking Smad2 signaling induced by TNF-α [ 42 ]. Chen et al found that loganin can reduce ROS and suppress the RAGE/p38 MAPK/NF-κB pathway to alleviate germ cell apoptosis in diabetes mellitus [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al verified that loganin alleviates intestinal epithelial inflammation by regulating the TLR4/NF-κB and JAK/STAT3 signaling pathways [ 41 ]. Chao et al exhibited that loganin has beneficial effects on Schwann cells by blocking Smad2 signaling induced by TNF-α [ 42 ]. Chen et al found that loganin can reduce ROS and suppress the RAGE/p38 MAPK/NF-κB pathway to alleviate germ cell apoptosis in diabetes mellitus [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the BL2 subtype does not respond to any classical treatment [48]. Taking these observations into consideration, the cytokines as well as calcitriol and its analogue could be inhibiting proliferation in SUM-229PE cells by inducing cell cycle arrest, as it has been observed in other tissues [4952]. This requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Loganin exhibits neuroprotection (Kwon et al, ), anti‐amnesic activity (Lee et al, ), protective effects against neurodegenerative diseases (Kwon, Kim, Lee, & Jang, ), hepatic injury, and other diabetic complications (Yamabe et al, ). In Schwann SW10 cells, Loganin blocks the effects of TNF‐α (Chao et al, ). Loganetin is produced by the deglucosylation of Loganin (Miettinen et al, ).…”
Section: Discussionmentioning
confidence: 99%